2018
DOI: 10.1002/chem.201803351
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Evolution by a Synthetic [FeFe] Hydrogenase Mimic Encapsulated in a Porphyrin Cage

Abstract: The design of a biomimetic and fully base metal photocatalytic system for photocatalytic proton reduction in a homogeneous medium is described. A synthetic pyridylphosphole‐appended [FeFe] hydrogenase mimic was encapsulated inside a supramolecular zinc porphyrin‐based metal–organic cage structure Fe4(Zn‐L)6. The binding is driven by the selective pyridine–zinc porphyrin interaction and results in the catalyst being bound strongly inside the hydrophobic cavity of the cage. Excitation of the capsule‐forming porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…136 In a similar fashion, Reek utilized Fe II -based cages built from Zn II -porphyrines for encapsulation of a variety of catalysts. [138][139][140] In these cages, the Zn II -porphyrine-based ligands play a dual function: with their four terminal diimine donors, they coordinate the Fe II vertices, and the central Zn II -cation contributes to catalyst encapsulation by coordinating the pyridine-donors included in the ligands of the catalyst. Especially for reactions in which the redox state and thus, the charge and coordination ability of the catalyst are changing, such additional anchors are quite important.…”
Section: Catalysis Inside Homoleptic Coordination Cagesmentioning
confidence: 99%
See 1 more Smart Citation
“…136 In a similar fashion, Reek utilized Fe II -based cages built from Zn II -porphyrines for encapsulation of a variety of catalysts. [138][139][140] In these cages, the Zn II -porphyrine-based ligands play a dual function: with their four terminal diimine donors, they coordinate the Fe II vertices, and the central Zn II -cation contributes to catalyst encapsulation by coordinating the pyridine-donors included in the ligands of the catalyst. Especially for reactions in which the redox state and thus, the charge and coordination ability of the catalyst are changing, such additional anchors are quite important.…”
Section: Catalysis Inside Homoleptic Coordination Cagesmentioning
confidence: 99%
“…In a recent study, Reek encapsulated a [FeFe] hydrogenase active site model compound with the aid of a pyridyl-phosphole ligand as anchor into such a cage. 139 This combination drives the photochemical proton reduction. In an electrochemical follow-up study, 138 the same authors utilized a slightly modified version of the diiron complex and identified a shift to lower overpotential of the [FeFe] catalyst as a result of encapsulation inside the cationic cage.…”
Section: Functional Homoleptic Cagesmentioning
confidence: 99%
“…In some cases, PS and WRC are combined into a single molecular photocatalyst. [10,35] We will discuss the potential of time-resolved infrared spectroscopy to investigate reaction mechanisms of molecule-based water reduction systems. The main focus will be on a water reduction system, whose reaction mechanism is rather well understood in solution, and we will discuss how the reaction mechanism changes once the system is brought onto a surface.…”
Section: Light Absorption and Excited State Lifetimementioning
confidence: 99%
“…The same tetrahedral assembly was used to encapsulate an [FeFe] hydrogenase mimic containing a pyridylphosphole moiety via Zn•••N coordination. 158 The system was applied in the light-harvesting hydrogen evolution reaction, in which the zinc-porphyrins served as photosensitizers allowing electron transfer to the encapsulated iron catalyst upon excitation (Scheme 34). Secondary Zn•••N coordination also drives the encapsulation of a chiral rhodium-coordinated phosphoramidite ligand inside Ribas's tetrahedral cage comprising zinc-porphyrins (Scheme 35).…”
mentioning
confidence: 99%